Breast Cancer: Immunohistochemical and Molecular Study of the HER-2 Oncoprotein in Congolese Women - Anicet Luc Magloire Boumba; Fabien Gaël Mouamaba; Sidney Frousse Christian Ngatali; Dimitry Moudiongui Mboungou Malanda; Donatien Moukassa; Jean Félix Peko (New Horizons in Medicine and Medical Research Vol. 5, 2022)
Introduction: Breast cancer is a diverse disease with a wide range of morphological and molecular characteristics that influence treatment response. Objective: The purpose of this study was to evaluate by immunohistochemistry and RT-PCR the overexpression of HER2 in breast cancer in women in the Republic of Congo. Materials and Methods: An 8-month cross-sectional descriptive study was carried out. 25 paraffin biopsies were taken from breast cancer patients at the University Hospital of Brazzaville. The epidemiological, clinical, histological, immunohistochemical, and molecular aspects of the disease were investigated. Results: The mean age of the patients was 49.64 ± 13.20 years (31-80 years). 60% of the patients had a right localization of the tumor. Invasive nonspecific type carcinoma was found in 76% of the patients. The T4b N1a M0 stage was the most common, accounting for 56% of the study population. Sixty percent of patients had SBR histopronostic grade 1. The percentages of positive oestrogen and progesterone receptors were 45 and 60%, respectively. The HER2 oncoprotein was found to be positive in 12% (3/25) of the 25 cases tested for IHC. With 32%, the luminal group was in the majority. RT-PCR analysis of the HER2 gene revealed overexpression in 60% (15/25) of cases, three of which were already positive for IHC. The "AmoyDx® HER2 Mutation Detection Kit" detected 12 mutations, 10 of which involved exon 20, accounting for 83.33 percent of cases, and 2 mutations involving exon 19, accounting for 16.67 percent of cases. The correlation of the overexpression of the HER2 gene showed a statistically significant difference between the two techniques, p <0.00003. Conclusion: Because HER2 is a prognostic and predictive marker in breast cancer, it is a promising therapeutic target. However, IHC’s highlighting remains time-consuming and prone to false negatives. As a result, when it comes to implementing targeted breast cancer therapies in Congo, molecular analysis could play a critical role in decision-making.